2008
DOI: 10.1111/j.1600-0838.2007.00704.x
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to sport injury rehabilitation programs: an integrated psycho‐social approach

Abstract: The aim of the present study was to examine an adapted integrated psycho-social model to predict sport injury rehabilitation adherence. A longitudinal prospective design was used whereby 70 patients attending private physiotherapy clinics completed a battery of questionnaires both pre- and post-rehabilitation treatment based on the adapted framework. All participants were receiving treatment for tendonitis-related injuries. Adherence was monitored prospectively over the entire rehabilitation program using an o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
56
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(65 citation statements)
references
References 31 publications
3
56
1
1
Order By: Relevance
“…Collectively, the results involving self-presentation from studies 1 and 2 support previous research: intrapersonal factors highlighted in the Wiese-Bjornstal et al 9 model, such as self-efficacy, self-motivation, and personal coping, have been associated with rehabilitation adherence. 32,33 These findings also lend further credence to the contention that athletes who are worried about making desired impressions on others may engage in compensatory efforts by overadhering to their injury rehabilitation. Longitudinal research is needed to examine whether rehabilitation overadherence ultimately leads to negative consequences such as poor clinical rehabilitation (eg, insufficient physical healing, poor proprioception, muscular strength) and diminished return-to-sport outcomes (eg, reduced confidence in return to play abilities, poor postinjury performances).…”
Section: Discussionsupporting
confidence: 59%
“…Collectively, the results involving self-presentation from studies 1 and 2 support previous research: intrapersonal factors highlighted in the Wiese-Bjornstal et al 9 model, such as self-efficacy, self-motivation, and personal coping, have been associated with rehabilitation adherence. 32,33 These findings also lend further credence to the contention that athletes who are worried about making desired impressions on others may engage in compensatory efforts by overadhering to their injury rehabilitation. Longitudinal research is needed to examine whether rehabilitation overadherence ultimately leads to negative consequences such as poor clinical rehabilitation (eg, insufficient physical healing, poor proprioception, muscular strength) and diminished return-to-sport outcomes (eg, reduced confidence in return to play abilities, poor postinjury performances).…”
Section: Discussionsupporting
confidence: 59%
“…Second, the Sport Injury Rehabilitation Adherence Scale was utilized to assess adherence during clinic-based rehabilitation sessions. A total clinic rehabilitation adherence score was derived from summing each of the SIRAS responses for each item”35…”
Section: Resultsmentioning
confidence: 99%
“…This is consistent with previous findings indicating a relationship between increased self-efficacy, and adherence. 16,[38][39][40] Levy et al 38,40 found that belief in the efficacy of treatment significantly predicted clinical rehabilitation adherence, and that task support from the clinician and being self-efficacious were perceived to aid adherence in recreational athletes. In addition, Mannion et al 39 found a significant correlation with multidimensional adherence and self-efficacy in 37 patients suffering from low back pain.…”
Section: Discussionmentioning
confidence: 99%
“…Bandura 41 suggested that perceived self-efficacy determines the amount of effort invested and persistence in the face of obstacles. It is possible the current performance profiling goal setting intervention may have resulted in the therapist 'yielding' control of treatment to the patient, 38 thereby promoting self-efficacy and a series of performance accomplishments. 9 When comparing scores for treatment efficacy across the groups, no significant difference was found between the experimental goal setting group and either C1 or C2.…”
Section: Discussionmentioning
confidence: 99%